Ecological carrying capacity of Saanane Island proposed National Park, Mwanza, Tanzania - Nahonyo , CL; Sangu, G (Tanzania Journal of Science, 2017)
The study on ecological carrying capacity of Saanane Island aimed at assessing stocking capacity of the island to provide guidance to the introduction of animals to enhance its ecological value and tourism potential. To evaluate the ecological carrying capacity of the Island, wet and dry season data were collected in 2014 for woody, herbaceous and grass species using PCQ and quadrat methods Wet and dry weights biomass of the forage material was measured to determine dry matter content and are presented as dry weight biomass. Total productivity was 4,280 kg/ha dry weight in wet season which increased to 7,965 kg/ha dry weight in dry season due to absence of disturbance such as limited grazing and fire which is rarely practiced on the Island. Woody species had a total density of 491woody plants ha-1, which was not significant using unpaired two sample t test. This study suggest that the range capability of Saanane Island is 6.76 ha/ animal metabolic requirement (GU) for wet season and 9.125 ha/GU for dry season and thus the productivity of the Island is capable of sustaining 43.5 GU in wet season and 32.2 GU in dry season based on the size of the Island estimated to be 3 km2. Key words: Ecology, Carrying capacity, Saanane Island, forage, herbivore